Interactions Between Genes From Aging Pathways May Influence Human Lifespan and Improve Animal to Human Translation - Ukraintseva, Svetlana; Duan, Matt; Arbeev, Konstantin; Wu, Deqing; Bagley, Olivia; Yashkin, Arseniy P.; Gorbunova, Galina; Akushevich, Igor; Kulminski, Alexander; Yashin, Anatoliy (Frontiers in Cell and Developmental Biology, 2021)
A major goal of aging research is identifying genetic targets that could be used to slow or reverse aging- changes in the body and extend limits of human lifespan. However, majority of genes that showed the anti-aging and pro-survival effects in animal models were not replicated in humans, with few exceptions. Potential reasons for this lack of translation include a highly conditional character of genetic influence on lifespan, and its heterogeneity, meaning that better survival may be result of not only activity of individual genes, but also gene-environment and gene-gene interactions, among other factors. In this paper, we explored associations of genetic interactions with human lifespan. We selected candidate genes from well-known aging pathways (IGF1/FOXO growth signaling, P53/P16 apoptosis/senescence, and MTOR/SK6 autophagy and survival) that jointly decide on outcomes of cell responses to stress and damage, and so could be prone to interactions. We estimated associations of pairwise statistical epistasis between SNPs in these genes with survival to age 85+ in the Atherosclerosis Risk in Communities study, and found significant (FDR<0.05) effects of interactions between SNPs in IGF1R, TGFBR2, and BCL2 on survival 85+. We validated these findings in the Cardiovascular Health Study sample, with P<0.05, using survival to age 85+, and to the 90th percentile, as outcomes. Our results show that interactions between SNPs in genes from the aging pathways influence survival more significantly than individual SNPs in the same genes, which may contribute to heterogeneity of lifespan, and to lack of animal to human translation in aging research.